2017
DOI: 10.1038/s41467-017-01227-7
|View full text |Cite
|
Sign up to set email alerts
|

Elevated olivine weathering rates and sulfate formation at cryogenic temperatures on Mars

Abstract: Large Hesperian-aged (~3.7 Ga) layered deposits of sulfate-rich sediments in the equatorial regions of Mars have been suggested to be evidence for ephemeral playa environments. But early Mars may not have been warm enough to support conditions similar to what occurs in arid environments on Earth. Instead cold, icy environments may have been widespread. Under cryogenic conditions sulfate formation might be blocked, since kinetics of silicate weathering are typically strongly retarded at temperatures well below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 34 publications
(47 reference statements)
2
28
0
Order By: Relevance
“…The ice-weathering model suggested that the interior of ice deposits promotes acidic weathering of dust through cryo-concentration of sulfur-rich volcanic aerosols, leading to jarosite precipitation 13 , 14 . Experimental evidence has since shown that the weathering rate of basalt-related minerals is elevated at cryogenic temperatures 16 , in accordance with the identification of jarosite as a weathering product in Antarctica 17 . But the englacial formation of jarosite is still a speculation.…”
Section: Introductionsupporting
confidence: 58%
“…The ice-weathering model suggested that the interior of ice deposits promotes acidic weathering of dust through cryo-concentration of sulfur-rich volcanic aerosols, leading to jarosite precipitation 13 , 14 . Experimental evidence has since shown that the weathering rate of basalt-related minerals is elevated at cryogenic temperatures 16 , in accordance with the identification of jarosite as a weathering product in Antarctica 17 . But the englacial formation of jarosite is still a speculation.…”
Section: Introductionsupporting
confidence: 58%
“…Further recent interest in olivine dissolution rates stems from its potential role in the weathering of the Martian surface (e.g. Stopar et al, 2006;Olsen and Rimstidt, 2007;Hausrath et al, 2008;Hausrath and Brantley, 2010;Dehouck et al, 2014;Velbel, 2014;Olsen et al, 2015;Niles et al, 2017). Such interest has led to a large number of studies aimed at characterizing forsterite dissolution behavior and rates at various fluid compositions and temperatures (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They can partially explain why post-depositional processes affecting dust are so notable at this site. Dust deposited at Talos Dome has a local basaltic-doleritic signature (Baccolo et al, 2018a) and basalts are weatherable rocks, also at low temperature (Li et al, 2016;Niles et al, 2017).…”
Section: Englacial Weathering Of Dustmentioning
confidence: 99%